Literatur Review: Dampak Penggunaan Antibiotik Jangka Panjang terhadap Mikrobioma Tubuh Manusia - Rima Anggraini; Yuyun Amalia Caniago; Risdah Mahyuni; Widya Rahayu; Ros Mardiah; Nurul Hafizah Hasanah; Dinda Lestari Hasibuan; Muhammad Syafi`i; Miftahul Khairani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Antibiotics are one of the main pillars in the treatment of bacterial infections and have contributed significantly to increasing human life expectancy. However, long-term use of antibiotics has serious consequences for the balance of the body's microbiome, especially the gut microbiome which plays an important role in maintaining homeostasis through the regulation of the immune system, metabolism, and protection against pathogens. This literature review aims to comprehensively analyze the impact of long-term antibiotic use on the structure, diversity, and function of the human microbiome. The scientific articles reviewed were obtained from PubMed, Scopus, ScienceDirect, and Google Scholar databases, including empirical research, systematic review, and meta-analysis published in the last ten years. The results showed that prolonged exposure to antibiotics consistently decreased microbiota diversity, altered the composition of bacterial communities, and triggered dysbiosis, which is often persistent even when therapy is stopped. Dysbiosis is associated with impaired immune system function, increased systemic inflammation, risk of allergic and metabolic diseases, and potential disorders on the intestinal-brain axis. This impact is more pronounced in vulnerable groups such as neonates and children, especially when exposure occurs during a critical period of development. In conclusion, long-term antibiotic use has broad systemic implications, so a more rational, prudent, and sustainable use strategy is needed to maintain the health of the human microbiome.